2020
DOI: 10.1186/s12876-020-01394-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of BioFire FilmArray gastrointestinal PCR panel associated with reductions in antibiotic use, time to optimal antibiotics, and length of stay

Abstract: Background: Rapid and accurate diagnostic tools are needed for appropriate management of infectious diarrhea. Methods: We evaluated the impact of the introduction of rapid multiplex PCR testing using the FilmArray gastrointestinal (GI) panel (BioFire Diagnostics, LLC, Salt Lake City, UT) at our institution, and compared the results to those of standard stool cultures. Results: The most common pathogens detected by the FilmArray GI panel were Clostridium difficile (55.0%), Campylobacter species (20.9%), Salmone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…The main advantage of the BioFire ® GI Panel was that it was able to replace the five to six conventional stool testing methods available at the hospital, meanwhile maintaining high detection positivity rates for the 22 pathogens included in the panel. Like previous reports, the BioFire ® GI Panel showed a higher pathogen positivity rate than conventional stool tests in this study [ 17 , 25 ]. In fact, when BioFire ® GI Panel was compared to both conventional testing methods in the prospective and historical cohort, the detection positivity rates were significantly higher for both.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The main advantage of the BioFire ® GI Panel was that it was able to replace the five to six conventional stool testing methods available at the hospital, meanwhile maintaining high detection positivity rates for the 22 pathogens included in the panel. Like previous reports, the BioFire ® GI Panel showed a higher pathogen positivity rate than conventional stool tests in this study [ 17 , 25 ]. In fact, when BioFire ® GI Panel was compared to both conventional testing methods in the prospective and historical cohort, the detection positivity rates were significantly higher for both.…”
Section: Discussionsupporting
confidence: 87%
“…With the introduction of the BioFire ® GI Panel, there have been controversies on the actual benefit and impact that the test may have in treating patients with AGE. However, studies related to the clinical utility of these tests have been lacking and real-world data on children with AGE are important and urgent [ 17 , 24 ]. To our knowledge, this study is the first prospective study on the clinical utility of BioFire ® GI Panel in pediatric AGE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests have recently been shown to reduce time to appropriate antibiotic therapy and reduce length of stay when compared with conventional methods. 16 They also provide a cost benefit via reducing additional diagnostic stool tests and imaging studies. 5 Generally, the results of the GI panel in this study produced an observable difference in antibiotic therapy as those with negative panel results had reduced exposure to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated its utility within the hospital setting. Torres-Miranda et al 1 found that GIP testing led to decreased median hospital length of stay (LOS) by 4 days in patients with diarrhea. Furthermore, the mean time to appropriate antibiotic therapy was shortened by 24 hours in those who underwent GIP testing.…”
mentioning
confidence: 99%